Synthesis of C,N,N-Cyclometalated Gold(III) Complexes with Anionic Amide Ligands - Niizeki, Ryotaro; Higashida, Kosuke; Mejri, Emna; Sawamura, Masaya; Shimizu, Yohei (Synlett, 2021)
A series of neutral C,N,N Au(III) complexes were synthesized with N-(8-quinolinyl)benzamide derivatives or chiral N-[2-(1,3-oxazolin-2-yl)phenyl]benzamide derivatives. The convenient synthesis method for the amide ligands, together with their operationally simple complexation by direct C–H auration, permitted changes to both the steric and electronic properties of Au(III) complexes for promoting the catalytic three-component couplings of an aldehyde, an amine, and an alkyne.
Keywords: gold(III) complexes; ligands; pincer complexes; catalysts; multicomponent reactions; chiral complexes